2013
DOI: 10.1007/s10549-013-2611-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat necrosis of the breast in the accelerated partial breast irradiation era: the need for a universal grading system

Abstract: Fat necrosis of the breast is increasingly reported and used as a trial endpoint in the treatment of breast cancer with accelerated partial breast irradiation (APBI). Yet, there is no universal toxicity scoring system within the latest version of the Common Terminology Criteria for Adverse Events (CTCAE v4.0). This requires investigators to adopt their own scoring system or improperly use those that exist, and limits accurate reporting of this entity. Fat necrosis of the breast also creates diagnostic uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In non-IBC, HER2-enriched and triple-negative tumors have increased breast cancer-specific mortality in comparison with the other subtypes [ 7 , 8 ]. For IBC, a recent analysis of the American National Cancer Database showed that HR-positive disease was not associated with an advantageous prognosis, and HER2-enriched status was not correlated with unfavorable overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…In non-IBC, HER2-enriched and triple-negative tumors have increased breast cancer-specific mortality in comparison with the other subtypes [ 7 , 8 ]. For IBC, a recent analysis of the American National Cancer Database showed that HR-positive disease was not associated with an advantageous prognosis, and HER2-enriched status was not correlated with unfavorable overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Fat necrosis can negatively affect the quality of life of the patients because of poor cosmetic result and pain. Unfortunately, fat necrosis cannot be efficiently evaluated because there are no standard systems for grading [33]. Breast surgeons need to explain the severity and of frequency fat necrosis to the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of ADM is that it is composed of cells that are resistant to radiation and have already been applied irradiation. Radiation therapy is also a risk factor of fat necrosis [18].…”
Section: Discussionmentioning
confidence: 99%